Affordances - a Merleau-Pontian account - Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2006)
In this paper, the concept of ’affordance’ is given an ontological and epistemological explication building on a Merleau-Pontian view of human being as always already being-in-the world in a non-thematized, pre-reflective correspondence of body and world in the concrete activity. A dynamic, agent-centred, cultural-, experience- and skill-relative, but perception-independent, ontology is proposed for affordances. It is argued that this is more in line with the original Gibsonian understanding of the concept than a recent attempt by McGrenere and Ho, because the latter fall back upon the subject-object-dichotomy that Gibson was trying to transcend.